A randomized, intraindividual, non‐inferiority, Phase III study comparing daylight photodynamic therapy with BF‐200 ALA gel and MAL cream for the treatment of actinic keratosis. (14th August 2018) - Dirschka, T.; Ekanayake‐Bohlig, S.; Dominicus, R.; Aschoff, R.; Herrera‐Ceballos, E.; Botella‐Estrada, R.; Hunfeld, A.; Kremser, M.; Schmitz, B.; Lübbert, H.; Puig, S.
Abstract: Background: The most effective treatment modality for actinic keratosis (AK) is photodynamic therapy (PDT). Major obstacles of PDT are the need of a special illumination device and pain accompanying the illumination. These issues may be overcome by replacing an artificial high‐power light source with natural daylight for more extended illumination at lower light doses. Objective: To determine whether BF‐200 ALA (a nanoemulsion gel containing 7.8% 5‐aminolaevulinic acid) is non‐inferior to MAL (a cream containing 16% methyl‐aminolaevulinate) in the treatment of mild‐to‐moderate AK with daylight PDT (dPDT). Non‐inferiority of the primary efficacy variable (total lesion clearance rate per patient's side 12 weeks after PDT) is established if the mean response for BF‐200 ALA is no worse than for MAL, within a statistical margin of Δ = −12.5%. Methods: The study was performed as an intraindividual comparison with 52 patients in seven centres in Germany and Spain. Each patient received one dPDT. Results include clinical endpoints as well as 1‐year follow‐up results. Results: Twelve weeks after a single dPDT, 79.8% of the AK lesions treated with BF‐200 ALA gel and 76.5% of the lesions treated with MAL cream were completely cleared. The median of differences was 0.0 with a one‐sided 97.5% CI of 0.0, establishing non‐inferiority ( P < 0.0001). Results for secondary efficacy parameters were in line with the primary outcome. Recurrence rates 1 year after the treatment were 19.9% for lesions treated with BF‐200 ALA and 31.6% for lesions treated with MAL. Adverse reactions including pain were mostly mild and transient and identical to those previously described for dPDT. Conclusion: Daylight PDT of AK with BF‐200 ALA is well‐tolerated and non‐inferior to MAL/dPDT. The study demonstrates a trend towards higher efficacies after 3 months and significantly lower recurrence rates after 1 year follow‐up.